microRNA-22, downregulated in hepatocellular carcinoma and correlated with prognosis, suppresses cell proliferation and tumourigenicity - Zhang, J (Nature Publishing Group, 2010)
BACKGROUND: Recently, microRNAs in cancer development have attracted much attention, but their roles in tumorigenesis are still largely unknown. In this study, a functional role of miR-22 in hepatocellular carcinoma (HCC) development has been identified. METHODS: Quantitative real-time PCR was used to determine the level of miR-22 transcript in HCC clinical samples, and its correlation with disease-free survival was determined using Kaplan–Meier method. Restoration of miR-22 expression was carried out in HCC cell lines to assess its influence on HCC cell proliferation and tumourigenicity. RESULTS: In the 160 paired HCC tissue samples, miR-22 expression was downregulated in HCC, and low miR-22 expression in HCC was predictive of poor survival in HCC patients. Functional studies indicated that ectopic expression of miR-22 significantly inhibits HCC cell proliferation and tumourigenicity. Furthermore, histone deacetylase 4 (HDAC4), known to have critical roles in cancer development, was proved to be directly targeted and regulated by miR-22. Furthermore, HDAC4 was upregulated in miR-22-downregulated HCC tissues, suggesting that downregulation of miR-22 might participate in HCC carcinogenesis and progression through potentiation of HDAC4 expression. In addition, cell proliferation was also suppressed by knockdown of HDAC4 or treatment with HDAC inhibitor trichostatin A in HCC cell lines. CONCLUSION: miR-22, downregulated in HCC, has an anti-proliferative effect on HCC cells both in vitro and in vivo. Furthermore, miR-22 may have considerable potential in identification of the prognosis and application of cancer therapy for HCC patients.